Variability for seed longevity among advanced breeding lines of soybean (Glycine max) - S.K. LAL; S.K. JAIN; K.P. SINGH; AKSHAY TALUKDAR; R.L. SAPRA (Seed Research, 2026)
The correlation between results of field emergence and accelerated aging test (0.664*) and the correlation between accelerated seed ageing and grain yield kg/ha (0.745*) were highly significant in the advanced soybean breeding lines tested. The genotypes showing more than 90% germination under accelerated aging test yielded more than 20 q/ha, whereas the genotypes which exhibited poor germination (<70%) under accelerated aging test yielded less than 15 q/ha. Since plant stand is determined by the seed longevity, its high correlation with grain yield is important. Thus, selection for better seed longevity will be of great help in indirect selection for higher yield. Apart from achieving higher yield, selection for good seed longevity will be beneficial to the farmers.